Density-dependent spatial patterning of woody plants differs between a semi-arid and a mesic savanna in South Africa. (October 2018) - Hesselbarth, M.H.K.; Wiegand, K.; Dreber, N.; Kellner, K.; Esser, D.; Tsvuura, Z.
Abstract: Savannas can be defined by the co-dominance of grasses and trees. Interactions between these two life forms are relatively well studied, whereas tree-tree interactions attracted increased attention only recently. However, the influence of woody plant density on tree-tree interactions is rarely considered. We studied tree-tree interactions in a semi-arid and a mesic savanna to test for differences between open and dense woody vegetation in relation to broad-scale environmental conditions. We applied spatial point pattern analysis to gain a better understanding of processes, such as competition, facilitation and disturbances, affecting the spatial distribution of trees. Competition between trees was most pronounced in dense vegetation, whereas facilitation effects were more common in open vegetation. Further, we found that factors shaping the spatial patterns differ with scale. At short tree-to-tree distances, results indicate limited seed dispersal as the most influential factor explaining the spatial distribution of trees. However, with increasing tree-to-tree distances, environmental heterogeneity in the semi-arid savanna and disturbances in the mesic savanna became more important. We conclude that studying tree-tree interactions in savannas should explicitly consider the actual woody plant density, especially when different savanna types are compared. Highlights: Woody plant densities have an influence on tree-tree interactions. Tree-tree interactions are present in savannas. Interactions occur at different spatial scales and in relation to tree density. Tree-tree competition was most pronounced in dense savanna vegetation. Tree-tree facilitation effects were more common in open savanna vegetation.